Fernández, J. (2019). Memory: a self-referential account. Oxford University Press - Álvarez Céspedes, Juan Fernando (Estudios de Filosofía, 2021)
Fernández’ most recent book constitutes an articulated development of several philosophical considerations on memory displayed in previous, and forthcoming publications. The result of such articulated development ends up being a consistent account that provides an innovative and thought-provoking perspective on episodic remembering. This volume not only gathers and articulates the author’s previous ideas, but also provides new reflections, and objections that encompasses four significant domains in the philosophy of memory. In the first part of the book (Chapters 1, 2, and 3), Fernández offers an account of both the metaphysics and the intentionality of episodic memory; in the second part (Chapters 4 and 5), the author deals with certain phenomenological aspects involved in remembering; in the third part (Chapters 6 and 7), two important debates in the epistemology of memory are discussed.